2000
DOI: 10.1111/j.1095-8312.2000.tb00207.x
|View full text |Cite
|
Sign up to set email alerts
|

Speciation of Phlebotomus sandflies of the subgenus Larroussius coincided with the late Miocene-Pliocene aridification of the Mediterranean subregion

Abstract: The phylogeny and mode of speciation of hlediterranean Plr1ebotontu.r of the subgenus Lnr-iuussiu.c u ere inferred by comparative sequence analyses of a fragment of mitochondria] DNA (Cytochrome b) and of a nuclear gene (Elongation factor alpha). The molecular phylogenies were congruent basally, where their clades matched the species complexes defined by a few genitalic characters of each sex. Reticulate evolution was suggested for the most drrived species complex (Phlebotornus pcm2ciosz1s): the molecular phyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
69
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 34 publications
3
69
0
Order By: Relevance
“…3) (Rioux & Golvan, 1969) and for the survival of diapausing larvae in the winter (Ready & Croset, 1980). Intraspecific gene introgression could have occurred following postglacial dispersal from Mediterranean refugia, some 12,000 years ago for the last such possible event (Esseghir et al, 2000). For temperate animals and plants, Hewitt (1996Hewitt ( , 1999 proposed three broad patterns of postglacial dispersal into northern Europe from southern refugia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3) (Rioux & Golvan, 1969) and for the survival of diapausing larvae in the winter (Ready & Croset, 1980). Intraspecific gene introgression could have occurred following postglacial dispersal from Mediterranean refugia, some 12,000 years ago for the last such possible event (Esseghir et al, 2000). For temperate animals and plants, Hewitt (1996Hewitt ( , 1999 proposed three broad patterns of postglacial dispersal into northern Europe from southern refugia.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was reported, without detailed results or analysis, by Mahamdallie et al (2003). Therefore, mitochondrially, the populations of P. perniciosus from France belonged to the typical lineage (Esseghir et al, 1997(Esseghir et al, , 2000, and not to the Iberian lineage, which contained the haplotypes found in the E_T_TOR population from northeast Spain (Fig. 3).…”
Section: Comparative Sequence Analysis Of Mitochondrial Cyt B Of P Pmentioning
confidence: 95%
See 1 more Smart Citation
“…The term "evolutionary fit" has been used (Killick-Kendrick 1985), but Esseghir et al (2000) concluded that clear distinctions have not always been drawn between co-association (with the transmission cycle having a distinctive "landscape epidemiology"), co-evolution (e.g. between molecules of the sand fly midgut and the parasite external surface) and vector-parasite cospeciation (or co-cladogenesis).…”
mentioning
confidence: 99%
“…infantum, perhaps because some strains of this parasite have been associated with cutaneous rather than visceral human disease. The mode of speciation of Mediterranean Larroussius has recently been inferred from comparative sequence analyses not only of mtDNA but also of a nuclear gene, elongation factor alpha (Esseghir et al 2000). The molecular phylogenies were congruent basally, where their clades matched species complexes defined by a few genitalic characters of each sex.…”
mentioning
confidence: 99%